2002
DOI: 10.1046/j.1471-0307.2002.00065.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of enzymatic cross‐linking of milk proteins on functional properties of set‐style yoghurt

Abstract: This paper presents research on the effect of enzymatic cross‐linking of milk proteins on the properties of yoghurt. Whole milk was incubated with transglutaminase (TG) prior to fermentation (2 h, 40°C, E/S ratio 1/2000). Enzyme action was stopped by heating (1 min, 80°C). Skim‐milk was treated by simultaneous use of TG and thermophilic yoghurt starter culture without inactivation of the enzyme. A TG treatment of milk prior to fermentation led to prolonged fermentation, while the concomitant use of TG and cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
161
3
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(198 citation statements)
references
References 12 publications
27
161
3
7
Order By: Relevance
“…The tan δ profile during acidification of pre-heated micellar casein/ WPI mixtures in SMUF had a maximum at pH 5.03 ± 0.04, which was similar to that in acid gels formed from heated skim milk [20]. The solubilisation of calcium phosphate has been suggested to partially loosen the bonds between the protein particles in the acid gel network resulting in the maximum in tan δ [22]. No such tan δ maximum was observed when incubated with Tgase.…”
Section: Effect Of Tgase On the Properties Of Micellar Casein On Acidmentioning
confidence: 71%
See 1 more Smart Citation
“…The tan δ profile during acidification of pre-heated micellar casein/ WPI mixtures in SMUF had a maximum at pH 5.03 ± 0.04, which was similar to that in acid gels formed from heated skim milk [20]. The solubilisation of calcium phosphate has been suggested to partially loosen the bonds between the protein particles in the acid gel network resulting in the maximum in tan δ [22]. No such tan δ maximum was observed when incubated with Tgase.…”
Section: Effect Of Tgase On the Properties Of Micellar Casein On Acidmentioning
confidence: 71%
“…However, the presence of active Tgase during the acidification step markedly increased the final gel strength compared to the situation where the Tgase was inactivated prior to acidification. Lorenzen et al [22] found markedly increased gel strength in yoghurt (made from whole milk preheated at 92°C for 5 min) containing active Tgase compared to yoghurt made from preheated skim milk that was incubated with Tgase but with the enzyme then inactivated. The current work suggested that the action of Tgase at neutral pH (intra-micellar cross-linking) affected the stability of micellar casein to increased acidity (see Fig.…”
Section: Effect Of Tgase On the Properties Of Micellar Casein On Acidmentioning
confidence: 99%
“…Transglutaminase (TGase) can induce interaction through inter-and intra-molecular bonds in the protein molecules, resulting in formation of high molecular weight protein polymers and modification of the properties of the proteins and food products containing them (Nielsen et al 1995;Motoki and Seguro 1998). TGase had been applied in some dairy products including yoghurt (Faergemand and Qvist 1997;Lorenzen, et al 2002), but a need exists to study other enzyme systems capable of improving the quality of dairy products. Horseradish peroxidase (HRP, EC 1.11.1.7), a heme-containing enzyme from the tissue of edible horseradish (Yuan and Jiang 2003), can induce cross-linking of the proteins in the presence of H 2 O 2 and a low molecular weight hydrogen donor (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Cross-linking of milk proteins using a mixture containing horseradish peroxidase, glucose oxidase, and glucose can bring about higher hardness and adhesiveness to the yoghurt (Chang, Kong, & Zhao, 2014). The results from two past studies indicated that the yoghurt gels generated from the TGase-treated milk had significantly lower syneresis than the control yoghurt gels (Lorenzen et al, 2002;Şanlı et al, 2011). Cross-linking of milk proteins with three oxidases (Hiller & Lorenzen, 2011), or with the mixture containing horseradish peroxidase, glucose oxidase, and glucose (Chang et al, 2014) before yoghurt fermentation, has been proved to result in decreased whey drainage.…”
Section: Chemical Compositions Of Yoghurt Samplesmentioning
confidence: 99%
“…whey drainage). Traditional methods used to improve yoghurt texture and to decrease yoghurt syneresis include enrichment of dry matter (total solids) and/or protein contents, as well as the use of food hydrocolloids like gelatin (Lorenzen, Neve, Mautner, & Schlimme, 2002). In addition, yoghurt quality can also be improved at a molecular level via forming covalent bonds between or within milk proteins (Faergemand, Sørensen, Jørgensen, Budolfsen, & Qvist, 1999).…”
Section: Introductionmentioning
confidence: 99%